**Answer:**

see explanation

**Step-by-step explanation:**

(a)

10x - 45 ← factor out 10 from each term

= 10(x - 4.5)

(b)

- 2x + 3 ← factor out - 2 from each term

= - 2(x - 1.5)

(c)

- x + 4 ← factor out - 1 from each term

= - 1(x - 4)

(d)

- x - 19 ← factor out - 1 from each term

= - 1(x + 19)

**Answer:**

x=9.064

**Step-by-step explanation:**

**Answer:**

100%

**Step-by-step explanation:**

6 possibilities: 3 odd and 3 even

P(odd or even) 6/6= 100%

**Answer:**

**y = 2x^2 + 4x - 2 **

**Step-by-step explanation:**

y=2(x+1)^(2)-4 is in vertex form. We want the same equation in standard form, which looks like y = ax^2 + bx + c.

Perform the indicated multiplication (squaring of x + 1):

y = 2(x^2 + 2x + 1) - 4, or

y = 2x^2 + 4x + 2 - 4, or

**y = 2x^2 + 4x - 2 ** This is in the standard form of a quadatic.

I believe the answer is $532.8.

All I did was multiply 0.06 by 8,880.